ПОНИМАНИЕ АДМИНИСТРАТИВНОГО МОЛЧАНИЯ: ВЗГЛЯД ГОСУДАРСТВЕННЫХ СЛУЖАЩИХ ИЗ ПРИКАРПАТЬЯ - Юрковска-ГомулкаАгата; Курчевски, Камилла; Курзенпа-ДедоКатажина (Вопросы государственного и муниципального управления, 2020)
This paper presents attitudes of public officers employed in public administrative institutions in Subcarpathia (a region in southeast Poland) towards administrative silence. As a background to the problem, the paper provides characteristics of the legal environment in which the Polish public administration operates regarding administrative silence. In the Polish legal system, administrative silence is expressed and described by different linguistic terms; there are also a variety of possible reactions to it. It causes not only different interpretations of legal regulation concerning the silence, but it also prevents a universal application of these provisions by public administration. The research aimed at determining what kinds of situations are recognised by Subcarpathian public officers as administrative silence (as defined in the Polish Administrative Procedure Code), what types of reactions towards administrative silence most frequently occur, and if there are any internal measures to counteract the silence. The paper concludes with the authors’ assessment of the appropriateness of the current Polish regulatory framework on administrative silence for everyday practice of regional public administration in Subcarpathia. The authors conclude that legislation does not facilitate Subcarpathian public officers to correctly understand the consequences of administrative silence. This conclusion can be broadened to public administration in other Polish regions.